Preparation method and application of microencapsulation modified efficient intumescent flame-retardant system
By forming microencapsulated ammonium polyphosphate in epoxy resin and compounding it with other components, the problem of flammable and poor compatibility of epoxy resins is solved, and efficient expansion flame retardant performance is achieved, which significantly improves the performance of the expansion type. Improves the flame retardant properties and thermal stability of the material.
Patent Information
- Application Number
- CN202411180529.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-27
- Publication Date
- 2024-12-13
AI Technical Summary
Epoxy resin is flammable and has poor flame retardant properties, which limits its application in the field of high flame retardant requirements. The existing ammonium polyphosphate as an inorganic flame retardant system is poor in compatibility and easy to absorb water in epoxy resin, resulting in the mechanical properties of the material. and the flame retardant efficiency is reduced, and the high-efficiency expansion flame retardant system is lacking.
SiO2@APP was prepared by adding ammonium polyphosphate to the silica capsule solution to carry out in situ polymerization reaction, forming microencapsulated ammonium polyphosphate (SiO2@APP) and compounding it with melamine cyanurate and calcium gluconate to prepare SiO2@APP /MCA/CaG expanded flame retardant system to improve flame retardant performance.
It effectively improves the compatibility and flame retardant effect of the material, enhances the carbon residue rate and thermal stability, reduces the peak heat release rate and the total heat release amount, and achieves excellent flame retardant performance.
Smart Images

Figure CN119119581A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of fireproof and flame retardant systems, and in particular relates to a preparation method of a microencapsulated and modified high-efficiency intumescent flame retardant system and application thereof. Background Art
[0002] Epoxy resin (EP), due to the various functional groups in its chemical structure, has excellent properties, including excellent bonding, corrosion resistance, formability and thermal stability, etc., and has shown a wide range of application value in many fields such as adhesives, coatings and civil engineering. However, EP is mainly composed of three elements: carbon, hydrogen and oxygen, so its essential characteristic is flammability. Once the combustion conditions are met, it will burn violently and release toxic smoke and a large amount of heat, posing a huge threat to people's life and property safety. In addition, due to the poor flame retardant performance of EP, its application in fields with high flame retardant requirements is limited. Therefore, in order to improve the safety performance of EP materials and meet their application in fields with high flame retardant level requirements, it is very important to strengthen the flame retardant properties of EP.
[0003] As an inorganic phosphorus flame retardant system, ammonium polyphosphate (APP) has been applied by many scholars to the flame retardant research of epoxy resin due to its low cost, low toxicity and good flame retardant effect. However, when APP is added to the EP matrix as an inorganic flame retardant system, its compatibility is poor and it easily absorbs moisture in the air, which then migrates to the surface of the material and causes loss, thus reducing the mechanical properties and flame retardant efficiency of the EP composite material.
[0004] At present, there is no efficient intumescent flame retardant system based on microencapsulated ammonium polyphosphate (SiO2@APP). Summary of the invention
[0005] The present invention is proposed to solve the problems existing in the prior art, and its purpose is to provide a preparation method of a microencapsulated modified high-efficiency intumescent flame retardant system and its application.
[0006] The technical solution of the present invention is: a method for preparing a microencapsulated modified high-efficiency intumescent flame retardant system, comprising the following contents:
[0007] Adding ammonium polyphosphate (APP) and an emulsifier into a silica (SiO2) capsule material solution to carry out an in-situ polymerization reaction, a microencapsulated high-efficiency flame retardant system with ammonium polyphosphate (APP) as a core material and silica (SiO2) as a capsule material is obtained, namely, microencapsulated ammonium polyphosphate (SiO2@APP);
[0008] The SiO2@APP / MCA / CaG intumescent flame retardant system was formed by compounding melamine cyanurate (MCA), calcium gluconate (CaG) and microencapsulated ammonium polyphosphate (SiO2@APP).
[0009] Furthermore, the preparation method of SiO2@APP / MCA / CaG intumescent flame retardant system is as follows:
[0010] A. Add ionized water and anhydrous ethanol and heat to 45°C;
[0011] B. Add ammonium polyphosphate (APP) to the mixed solution and stir and disperse the emulsifier evenly;
[0012] C. Continue to add ammonia water and adjust the pH value to 9-10;
[0013] D. Continue to add ethyl orthosilicate dropwise;
[0014] E. Stir the reaction at 45°C for 2 hours, filter, and wash with deionized water and anhydrous ethanol;
[0015] F. Dry in a drying oven at 80°C for 24 hours to obtain microencapsulated ammonium polyphosphate (SiO2@APP);
[0016] G. Add melamine cyanurate (MCA) and calcium gluconate (CaG) to obtain an intumescent flame retardant system.
[0017] Furthermore, the components of the microencapsulated ammonium polyphosphate (SiO2@APP) and the proportions of each component are as follows:
[0018]
[0019] Furthermore, in step A, ionized water and anhydrous ethanol are added and the temperature is raised to 45° C. The specific process is as follows:
[0020] First, 40 parts of deionized water and 112 parts of anhydrous ethanol were added to a 500 mL three-necked flask equipped with a reflux condenser, a thermometer, and a stirrer;
[0021] Then, heat to 45°C in a water bath.
[0022] Furthermore, in step B, ammonium polyphosphate (APP) is added to the mixed solution, and the emulsifier is stirred and dispersed uniformly. The specific process is as follows:
[0023] First, add 50 parts of ammonium polyphosphate (APP) and 0.5 parts of emulsifier to the beaker solution;
[0024] Then, stir and disperse evenly.
[0025] Furthermore, step D continues to add ethyl orthosilicate dropwise, and the specific process is as follows:
[0026] 19.85 parts of ethyl orthosilicate were added dropwise to the system solution with a pH value of 9 to 10 within 30 minutes.
[0027] Furthermore, step E is stirred at 45° C. for 2 hours, filtered, and washed with deionized water and anhydrous ethanol. The specific process is as follows:
[0028] First, place the beaker in a 45°C constant temperature water bath and continue the reaction for 2 h;
[0029] Then, the stirring speed during the reaction was 700 r / min;
[0030] Then, filter to obtain a white precipitate, namely microencapsulated ammonium polyphosphate (SiO2@APP);
[0031] Finally, wash with deionized water and anhydrous ethanol.
[0032] Furthermore, in step G, melamine cyanurate (MCA) and calcium gluconate (CaG) are added to obtain an intumescent flame retardant system, and the specific process is as follows:
[0033] First, 0-5 parts of melamine cyanurate (MCA) were added to 0-20 parts of microencapsulated ammonium polyphosphate (SiO2@APP);
[0034] Then, 0-5 parts of calcium gluconate (CaG) are added to obtain an intumescent flame retardant system.
[0035] The application of microencapsulated modified high-efficiency intumescent flame retardant system includes the following:
[0036] Firstly, microencapsulated ammonium polyphosphate (SiO2@APP), melamine cyanurate (MCA) and calcium gluconate (CaG) were added into epoxy resin (EP) a glue in a certain proportion and stirred to disperse evenly;
[0037] Then, add epoxy resin (EP) b glue at a mass ratio of a:b=3:1, let it stand for 5 minutes, pour it into a silicone mold of specified size after the bubbles dissipate, and cure it at room temperature for 24 hours;
[0038] Finally, the flame retardant EP composite material is demoulded.
[0039] Furthermore, the flame retardant EP composite material components and the number of each component are as follows:
[0040]
[0041] The beneficial effects of the present invention are as follows:
[0042] The present invention performs microcapsule encapsulation modification on APP and adopts SiO2 as the capsule material, which can effectively encapsulate APP, improve the compatibility of the base material, and further improve the flame retardant effect thereof.
[0043] The present invention utilizes the condensed phase flame retardant mechanism of SiO2@APP and MCA and the gas phase flame retardant mechanism of SiO2@APP and CaG. The combination of the two can effectively improve the carbon residue rate and thermal stability of the material, and the flame retardant effect is better than when the two are used alone.
[0044] The present invention optimizes the ratio of the SiO2@APP, MCA and CaG intumescent flame retardant system, effectively reduces the peak value of the heat release rate and the total heat release of the material, and the material has good self-extinguishing property and excellent flame retardant performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Figure 1 1 is a cone calorimetry analysis diagram of EP and EP composite materials in an embodiment of the present invention, wherein (a) is an HRR curve and (b) is a THR curve;
[0046] Figure 2 : are SEM images of the embodiments of the present invention, wherein (a) and (b) are SEM images of SiO2@APP / EP, and (c) and (d) are SEM images of SiO2@APP / MCA / CaG / EP;
[0047] Figure 3 are digital photos of carbon residues in the embodiments of the present invention, wherein (a) is a digital photo of carbon residues of EP, (b) is a digital photo of carbon residues of SiO2@APP / EP, and (c) is a digital photo of carbon residues of SiO2@APP / MCA / CaG / EP;
[0048] Figure 4 TG and DTG curves in the embodiments of the present invention, wherein (a) is the TG curve of EP and EP composite material under nitrogen, and (b) is the DTG curve of EP and EP composite material under nitrogen. DETAILED DESCRIPTION
[0049] Hereinafter, the present invention will be described in detail with reference to the accompanying drawings and embodiments:
[0050] like Figures 1 to 4 As shown, the preparation method of the microencapsulated modified high-efficiency intumescent flame retardant system includes the following contents:
[0051] Adding ammonium polyphosphate (APP) and an emulsifier into a silica (SiO2) capsule material solution to carry out an in-situ polymerization reaction, a microencapsulated high-efficiency flame retardant system with ammonium polyphosphate (APP) as a core material and silica (SiO2) as a capsule material is obtained, namely, microencapsulated ammonium polyphosphate (SiO2@APP);
[0052] The SiO2@APP / MCA / CaG intumescent flame retardant system was formed by compounding melamine cyanurate (MCA), calcium gluconate (CaG) and microencapsulated ammonium polyphosphate (SiO2@APP).
[0053] The preparation method of SiO2@APP / MCA / CaG intumescent flame retardant system is as follows:
[0054] A. Add ionized water and anhydrous ethanol and heat to 45°C;
[0055] B. Add ammonium polyphosphate (APP) to the mixed solution and stir and disperse the emulsifier evenly;
[0056] C. Continue to add ammonia water and adjust the pH value to 9-10;
[0057] D. Continue to add ethyl orthosilicate dropwise;
[0058] E. Stir the reaction at 45°C for 2 hours, filter, and wash with deionized water and anhydrous ethanol;
[0059] F. Dry in a drying oven at 80°C for 24 hours to obtain microencapsulated ammonium polyphosphate (SiO2@APP);
[0060] G. Add melamine cyanurate (MCA) and calcium gluconate (CaG) to obtain an intumescent flame retardant system.
[0061] The components of the microencapsulated ammonium polyphosphate (SiO2@APP) and the number of each component are as follows:
[0062]
[0063] Step A: Add ionized water and anhydrous ethanol and heat to 45°C. The specific process is as follows:
[0064] First, 40 parts of deionized water and 112 parts of anhydrous ethanol were added to a 500 mL three-necked flask equipped with a reflux condenser, a thermometer, and a stirrer;
[0065] Then, heat to 45°C in a water bath.
[0066] Step B: Add ammonium polyphosphate (APP) to the mixed solution, and stir and disperse the emulsifier evenly. The specific process is as follows:
[0067] First, add 50 parts of ammonium polyphosphate (APP) and 0.5 parts of emulsifier to the beaker solution;
[0068] Then, stir and disperse evenly.
[0069] Step D: Continue to add ethyl orthosilicate dropwise, the specific process is as follows:
[0070] 19.85 parts of ethyl orthosilicate were added dropwise to the system solution with a pH value of 9 to 10 within 30 minutes.
[0071] Step E: Stir the reaction at 45°C for 2 hours, filter, and wash with deionized water and anhydrous ethanol. The specific process is as follows:
[0072] First, place the beaker in a 45°C constant temperature water bath and continue the reaction for 2 h;
[0073] Then, the stirring speed during the reaction was 700 r / min;
[0074] Then, filter to obtain a white precipitate, namely microencapsulated ammonium polyphosphate (SiO2@APP);
[0075] Finally, wash with deionized water and anhydrous ethanol.
[0076] Step G: adding melamine cyanurate (MCA) and calcium gluconate (CaG) to obtain an intumescent flame retardant system, and the specific process is as follows:
[0077] First, 0-5 parts of melamine cyanurate (MCA) were added to 0-20 parts of microencapsulated ammonium polyphosphate (SiO2@APP);
[0078] Then, 0-5 parts of calcium gluconate (CaG) are added to obtain an intumescent flame retardant system.
[0079] The application of microencapsulated modified high-efficiency intumescent flame retardant system includes the following:
[0080] Firstly, microencapsulated ammonium polyphosphate (SiO2@APP), melamine cyanurate (MCA) and calcium gluconate (CaG) were added into epoxy resin (EP) a glue in a certain proportion and stirred to disperse evenly;
[0081] Then, add epoxy resin (EP) b glue at a mass ratio of a:b=3:1, let it stand for 5 minutes, pour it into a silicone mold of specified size after the bubbles dissipate, and cure it at room temperature for 24 hours;
[0082] Finally, the flame retardant EP composite material is demoulded.
[0083] The flame retardant EP composite material components and the number of each component are as follows:
[0084]
[0085] Specifically, the application of the microencapsulated modified high-efficiency intumescent flame retardant system is as follows:
[0086] H. Add microencapsulated ammonium polyphosphate (SiO2@APP), melamine cyanurate (MCA), and calcium gluconate (CaG) and dissolve them in epoxy resin (EP) a glue;
[0087] I. Add epoxy resin (EP) b glue and let stand to defoam;
[0088] J. Pour into a silicone mold of specified size and solidify at room temperature;
[0089] K. After 24 hours, demoulding was performed to obtain a standard sample of flame-retardant EP composite material.
[0090] Specifically, in step H, microencapsulated ammonium polyphosphate (SiO2@APP), melamine cyanurate (MCA), and calcium gluconate (CaG) are dissolved in epoxy resin (EP) a glue, and the specific process is as follows:
[0091] First, microencapsulated ammonium polyphosphate (SiO2@APP), melamine cyanurate (MCA), and calcium gluconate (CaG) were added in the amounts of 0-20 parts, 0-5 parts, and 0-5 parts, with continuous stirring during the process;
[0092] Then, add it into 52.5 parts of epoxy resin (EP) a glue and stir to dissolve.
[0093] Specifically, step I adds epoxy resin (EP) b glue and stands to defoam. The specific process is as follows:
[0094] First, the ratio of epoxy resin (EP) a glue to epoxy resin (EP) b glue is 3:1;
[0095] Next, add 17.5 parts of epoxy resin (EP) b glue and let it stand for 5 minutes to defoam.
[0096] Embodiment 1
[0097] A method for preparing a microencapsulated modified ammonium polyphosphate high-efficiency intumescent flame retardant system comprises the following steps:
[0098] A. Add ionized water and anhydrous ethanol and heat to 45°C;
[0099] First, 40 parts of deionized water and 112 parts of anhydrous ethanol were added to a 500 mL three-necked flask equipped with a reflux condenser, a thermometer, and a stirrer;
[0100] Then, heat to 45°C in a water bath.
[0101] B. Add ammonium polyphosphate (APP) to the mixed solution and stir and disperse the emulsifier evenly;
[0102] First, add 50 parts of ammonium polyphosphate (APP) and 0.5 parts of emulsifier to the beaker solution; then, stir and disperse evenly.
[0103] C. Continue to add ammonia water to adjust the pH value to 9-10;
[0104] D. Continue to add ethyl orthosilicate;
[0105] The pH value of the beaker solution was adjusted to 9-10 using aqueous ammonia, and then 19.85 parts of ethyl orthosilicate was added dropwise over 30 minutes.
[0106] E. Stir the reaction at 45°C for 2 hours, filter, and wash with deionized water and anhydrous ethanol;
[0107] First, place the beaker in a 45°C constant temperature water bath and continue the reaction for 2 h;
[0108] Then, the stirring speed during the reaction was 700 r / min;
[0109] Then, filter to obtain a white precipitate, namely microencapsulated ammonium polyphosphate (SiO2@APP);
[0110] Finally, wash with deionized water and anhydrous ethanol.
[0111] F. Dry in a drying oven at 80°C for 24 hours to obtain microencapsulated ammonium polyphosphate (SiO2@APP);
[0112] G. adding melamine cyanurate (MCA) and calcium gluconate (CaG) in proportion to obtain an intumescent flame retardant system;
[0113] First, 0 parts of melamine cyanurate (MCA) was added to 20 parts of microencapsulated ammonium polyphosphate (SiO2@APP);
[0114] Then, 0 parts of calcium gluconate (CaG) was added to obtain an intumescent flame retardant system.
[0115] H. Add microencapsulated ammonium polyphosphate (SiO2@APP), melamine cyanurate (MCA), and calcium gluconate (CaG) and dissolve them in epoxy resin (EP) a glue;
[0116] First, 52.5 parts of epoxy resin (EP) a glue were placed in a beaker and heated to 50-60° C., with continuous stirring during the process;
[0117] Then, microencapsulated ammonium polyphosphate (SiO2@APP), microencapsulated ammonium polyphosphate (SiO2@APP), and melamine cyanurate (MCA) were added to the epoxy resin (EP) a glue in an amount of 20 parts, 0 parts, and 0 parts, and stirred while adding until they were completely dissolved.
[0118] I. Add epoxy resin (EP) b glue and let stand to defoam;
[0119] First, the ratio of epoxy resin (EP) a glue to epoxy resin (EP) b glue is 3:1;
[0120] Next, add 17.5 parts of EP b glue and let it stand for 5 minutes to defoam.
[0121] J. Pour into a silicone mold of specified size and solidify at room temperature;
[0122] The defoamed mixed solution was poured into silicone molds with sizes of 80 mm×10 mm×3 mm, 130 mm×13 mm×3 mm, and 100 mm×100 mm×3 mm, respectively.
[0123] K. After 24 hours, demoulding was performed to obtain the flame-retardant EP composite material standard sample S1, and various flame-retardant properties were tested.
[0124] Embodiment 2
[0125] A method for preparing a microencapsulated modified ammonium polyphosphate high-efficiency intumescent flame retardant system comprises the following steps:
[0126] A. Add ionized water and anhydrous ethanol and heat to 45°C;
[0127] First, 40 parts of deionized water and 112 parts of anhydrous ethanol were added to a 500 mL three-necked flask equipped with a reflux condenser, a thermometer, and a stirrer;
[0128] Then, heat to 45°C in a water bath.
[0129] B. Add ammonium polyphosphate (APP) to the mixed solution and stir and disperse the emulsifier evenly;
[0130] First, add 50 parts of APP and 0.5 parts of emulsifier to the beaker solution; then, stir and disperse evenly.
[0131] C. Continue to add ammonia water to adjust the pH value to 9-10;
[0132] D. Continue to add ethyl orthosilicate;
[0133] The pH value of the beaker solution was adjusted to 9-10 using aqueous ammonia, and then 19.85 parts of ethyl orthosilicate was added dropwise over 30 minutes.
[0134] E. Stir the reaction at 45°C for 2 hours, filter, and wash with deionized water and anhydrous ethanol;
[0135] First, place the beaker in a 45°C constant temperature water bath and continue the reaction for 2 h;
[0136] Then, the stirring speed during the reaction was 700 r / min;
[0137] Then, filter to obtain a white precipitate, namely microencapsulated ammonium polyphosphate (SiO2@APP);
[0138] Finally, wash with deionized water and anhydrous ethanol.
[0139] F. Dry in a drying oven at 80°C for 24 hours to obtain microencapsulated ammonium polyphosphate (SiO2@APP);
[0140] G. adding melamine cyanurate (MCA) and calcium gluconate (CaG) in proportion to obtain an intumescent flame retardant system;
[0141] First, 5 parts of melamine cyanurate (MCA) were added to 20 parts of microencapsulated ammonium polyphosphate (SiO2@APP);
[0142] Then, 0 parts of calcium gluconate (CaG) was added to obtain an intumescent flame retardant system.
[0143] H. Add microencapsulated ammonium polyphosphate (SiO2@APP), melamine cyanurate (MCA), and calcium gluconate (CaG) and dissolve them in epoxy resin (EP) a glue;
[0144] First, 52.5 parts of epoxy resin (EP) a glue were placed in a beaker and heated to 50-60° C., with continuous stirring during the process;
[0145] Then, microencapsulated ammonium polyphosphate (SiO2@APP), melamine cyanurate (MCA), and calcium gluconate (CaG) were added to the epoxy resin (EP) a glue in the amounts of 20 parts, 5 parts, and 0 parts, and stirred while adding until they were completely dissolved.
[0146] I. Add epoxy resin (EP) b glue and let stand to defoam;
[0147] First, the ratio of epoxy resin (EP) a glue to epoxy resin (EP) b glue is 3:1;
[0148] Next, add 17.5 parts of EP b glue and let it stand for 5 minutes to defoam.
[0149] J. Pour into a silicone mold of specified size and solidify at room temperature;
[0150] The defoamed mixed solution was poured into silicone molds with sizes of 80 mm×10 mm×3 mm, 130 mm×13 mm×3 mm, and 100 mm×100 mm×3 mm, respectively.
[0151] K. After 24 hours, demoulding was performed to obtain the flame-retardant EP composite material standard sample S2, and various flame-retardant properties were tested.
[0152] Embodiment 3
[0153] A method for preparing a microencapsulated modified ammonium polyphosphate high-efficiency intumescent flame retardant system comprises the following steps:
[0154] A. Add ionized water and anhydrous ethanol and heat to 45°C;
[0155] First, 40 parts of deionized water and 112 parts of anhydrous ethanol were added to a 500 mL three-necked flask equipped with a reflux condenser, a thermometer, and a stirrer;
[0156] Then, heat to 45°C in a water bath.
[0157] B. Add ammonium polyphosphate (APP) to the mixed solution and stir and disperse the emulsifier evenly;
[0158] First, add 50 parts of ammonium polyphosphate (APP) and 0.5 parts of emulsifier to the beaker solution;
[0159] Then, stir and disperse evenly.
[0160] C. Continue to add ammonia water to adjust the pH value to 9-10;
[0161] D. Continue to add ethyl orthosilicate;
[0162] The pH value of the beaker solution was adjusted to 9-10 using aqueous ammonia, and then 19.85 parts of ethyl orthosilicate was added dropwise over 30 minutes.
[0163] E. Stir the reaction at 45°C for 2 hours, filter, and wash with deionized water and anhydrous ethanol;
[0164] First, place the beaker in a 45°C constant temperature water bath and continue the reaction for 2 h;
[0165] Then, the stirring speed during the reaction was 700 r / min;
[0166] Then, filter to obtain a white precipitate, namely microencapsulated ammonium polyphosphate (SiO2@APP);
[0167] Finally, wash with deionized water and anhydrous ethanol.
[0168] F. Dry in a drying oven at 80°C for 24 hours to obtain SiO2@APP;
[0169] G. adding melamine cyanurate (MCA) and calcium gluconate (CaG) in proportion to obtain an intumescent flame retardant system;
[0170] First, 5 parts of melamine cyanurate (MCA) were added to 20 parts of microencapsulated ammonium polyphosphate (SiO2@APP);
[0171] Then, 5 parts of calcium gluconate (CaG) were added to obtain an intumescent flame retardant system.
[0172] H. Add microencapsulated ammonium polyphosphate (SiO2@APP), melamine cyanurate (MCA), and calcium gluconate (CaG) and dissolve them in epoxy resin (EP) a glue;
[0173] First, 52.5 parts of epoxy resin (EP) a glue were placed in a beaker and heated to 50-60° C., with continuous stirring during the process;
[0174] Then, microencapsulated ammonium polyphosphate (SiO2@APP), melamine cyanurate (MCA), and calcium gluconate (CaG) were added to the epoxy resin (EP) a glue in the amounts of 20 parts, 5 parts, and 5 parts, respectively, and stirred while adding until they were completely dissolved.
[0175] I. Add epoxy resin (EP) b glue and let stand to defoam;
[0176] First, the ratio of epoxy resin (EP) a glue to epoxy resin (EP) b glue is 3:1;
[0177] Next, add 17.5 parts of EP b glue and let it stand for 5 minutes to defoam.
[0178] J. Pour into a silicone mold of specified size and solidify at room temperature;
[0179] The defoamed mixed solution was poured into silicone molds with sizes of 80 mm×10 mm×3 mm, 130 mm×13 mm×3 mm, and 100 mm×100 mm×3 mm, respectively.
[0180] K. After 24 hours, demoulding was performed to obtain the flame-retardant EP composite material standard sample S3, and various flame-retardant properties were tested.
[0181] Comparative Example 1
[0182] Take 52.5 parts of epoxy resin (EP) a glue and 17.5 parts of epoxy resin (EP) b glue and put them in a beaker, stir them to make them evenly dispersed, let them stand for 5 minutes to defoam, pour them into a silicone mold of specified size, cure them at room temperature for 24 hours, demold them to obtain EP material standard sample B1, and test various flame retardant properties.
[0183] Comparative Example 2
[0184] Take 52.5 parts of epoxy resin (EP) a glue and put it in a beaker, heat it to 50-60℃, add 30 parts of ammonium polyphosphate (APP), and stir continuously during the addition process to disperse and dissolve it; add 17.5 parts of epoxy resin (EP) b glue and stir to disperse evenly, let it stand for 5 minutes to defoam, pour it into a silicone mold of specified size, cure it at room temperature for 24 hours, demold it to obtain EP material standard sample B2, and test various flame retardant properties.
[0185] Flame retardant performance test
[0186] Limiting oxygen index (LOI): According to the requirements of GB / T 2406.2-2009 "Determination of combustion behavior of plastics by oxygen index method Part 2 Room temperature test", the minimum oxygen concentration required for the combustion of flame-retardant EP composite materials is measured using a JF-3 oxygen index instrument, expressed as the volume percentage of oxygen. The sample is prepared strictly in accordance with the standard, and the sample size is 80mm×10mm×3mm.
[0187] Vertical combustion (UL-94): Prepare samples according to the requirements of GB / T 2408-2008 "Horizontal and vertical methods for determination of combustion performance of plastics". Use vertical combustion tester to determine the vertical combustion grade of flame retardant EP composite materials. The sample size is: 130mm×13mm×3mm.
[0188] Cone calorimetry test (CONE): According to the requirements of ISO5660-2002 "Fire tests - Heat release, smoke generation and mass loss rate", the combustion behavior of flame-retardant EP composite materials is measured using a cone calorimeter with a thermal radiation power of 50kW / m 2 , the sample size is 100mm×100mm×3mm.
[0189] Thermogravimetric analysis (TG): Thermogravimetric analysis (TG) experiments were carried out in a N2 environment. The heating rate was maintained at 20°C / min, and the temperature was gradually increased from room temperature to 800°C. The sample mass was ensured to be no less than 20 mg to ensure the accuracy of the test results.
[0190] Table 1 LOI and UL-94 test results of standard samples:
[0191]
[0192] From Table 1, we can get:
[0193] Sample B1 pure EP showed extremely high flammability in the air, and the combustion reaction was extremely violent. Its LOI value was only 18.9%, and it failed to reach any level in the vertical burning test. However, when ammonium polyphosphate (APP) was added to sample B2, the flame retardant performance of the EP composite material was significantly improved, and its LOI value jumped to 34.5%, and successfully reached the V-1 level in the vertical burning test.
[0194] After sample S1 SiO2@APP was doped with EP, the LOI of the EP composite material reached 36.5%, which was 93% and 6% higher than that of B1 pure EP and sample B2 APP / EP composite material at the same doping amount, respectively, and the UL-94 grade reached V-0, which indicates that the PN-Si synergistic flame retardant in the microcapsule flame retardant played a role.
[0195] Sample S2 incorporates SiO2@APP / MCA into EP, and the LOI of the EP composite material reaches 38.5%, which is 5% higher than that of the EP composite material of sample S1 that only incorporates SiO2@APP, and the UL-94 grade reaches V-0, which shows that the combination of SiO2@APP and MCA has a synergistic flame retardant effect.
[0196] After adding SiO2@APP / MCA / CaG intumescent flame retardant to sample S3, the VOL value of the EP composite material increased to 40.5%, and the UL-94 was still V-0, with the best flame retardant performance. In the vertical burning test of the final sample strip, it can be seen that the composite material has good self-extinguishing properties.
[0197] Table 2 Standard sample CONE test results:
[0198]
[0199] Depend on Figure 1 And Table 2 can be obtained:
[0200] Figure 1 (a) and (b) are the HRR and THR curves of EP composite materials over time. Figure 1 It can be seen that the PHRR value of sample B1 pure EP is very high, 761.3kW / m 2 Compared with sample B1, the PHRR values of APP / EP in sample B2, SiO2@APP / EP in sample S1 and SiO2@APP / MCA / CaG / EP in sample S3 were reduced by 78%, 86.2% and 92%, respectively, which shows that the addition of APP, SiO2@APP and SiO2@APP / MCA / CaG can improve the flame retardant properties of EP. Among them, the PHRR value of SiO2@APP / MCA / CaG / EP composite in sample S3 is the smallest, indicating that the intumescent flame retardant system in S3 has the most significant flame retardant effect on EP.
[0201] Figure 1The HRR curves of the three EP composite materials fluctuate less than those of pure EP, which indicates that the addition of the three flame retardant systems of APP in sample B2, SiO2@APP in sample S1, and SiO2@APP / MCA / CaG in sample S3 increases the residual carbon of the EP composite material, which slows down the thermal degradation of the EP composite material and reduces the heat release. Among them, the slope of the HRR curve of the SiO2@APP / MCA / CaG / EP composite material in sample S3 is the smallest, which indicates that the addition of the ternary expansion flame retardant system makes the residual carbon rate of the EP composite material reach the maximum and the flame retardant performance is the best. This is mainly because the SiO2@APP / MCA / CaG expansion system in sample S3 has a good synergistic flame retardant effect. In this expansion system, during the heating process of SiO2@APP, the SiO2 particles decomposed by the heat will adhere to the surface of the EP material to form an isolation barrier to isolate the heat transmission, and APP as an acid source can promote the dehydration of EP into carbon when heated, and can also work with MCA to play the flame retardant role of the gas source, releasing N2, NH3 and other flame-retardant gases to reduce the system temperature. At the same time, CaG, as a carbon source, decomposes under heat to form substances such as calcium oxide and calcium carbonate, which cover the surface of EP, inhibit the decomposition heat release and heat exchange of the composite material, thereby reducing the total heat release of the EP composite material.
[0202] Table 3 Test results of standard samples TG and DTG:
[0203]
[0204] Depend on Figure 2 , Figure 3 , Figure 4 And Table 3 can be obtained:
[0205] like Figure 4 As shown in the figure, the thermal degradation process of the three EP composite materials has only one stage, which is the rupture of the main chain in the EP structure at high temperature. The initial decomposition temperature of EP is 193℃. After adding flame retardants, the T -5% All of them increased, which shows that the three flame retardant systems can improve the thermal stability of EP materials under this ratio, among which SiO2@APP / MCA / CaG has the best thermal stability. Compared with comparative examples B1 and B2, the addition of SiO2@APP / MCA / CaG in standard sample S3 can improve the thermal stability and carbon residue rate of EP materials, making the carbon residue rate of EP composite material 34.8% at 600℃. The carbon residue of pure EP in sample B1 ( Figure 3 (a) There is almost no residual amount and you can even see the bottom of the mold. This is because pure EP is highly flammable and has poor carbonization performance. However, the residual carbon amount of SiO2@APP / MCA / CaG / EP composite in sample S3 is significantly increased and shows tight and firm properties ( Figure 3This is attributed to the synergistic flame retardant effect of the SiO2@APP / MCA / CaG intumescent flame retardant system in the composite material of sample S3, in which the P-containing fragments in APP, SiO2 particles and CaG have a carbonization effect.
[0206] As Figure 1 As shown in Figure 2, the carbon residue of the composite material of sample S1 has increased, but the carbon layer structure is discontinuous and there are many cracks. Figure 2 (a) and (b), as the amount of gas released in the system increases, these cracks provide channels for subsequent heat propagation and diffusion of combustible gases, accelerating the degradation of EP composites and reducing the flame retardant efficiency.
[0207] like Figure 2 As shown in (c) and (d), the residual carbon structure of the composite material of sample S3 is more dense and continuous, with almost no cracks, which indicates that its structural strength is higher. The structure is honeycomb-shaped and has many completely closed holes (in the red rectangular frame). These holes increase the specific surface area of the residual carbon and form a denser protective carbon layer, which has an important impact on the propagation of heat and the diffusion of combustible and combustion-supporting gases, making the SiO2@APP / MCA / CaG / EP composite material in sample S3 have significant condensed phase flame retardancy.
[0208] The present invention performs microcapsule encapsulation modification on APP and adopts SiO2 as the capsule material, which can effectively encapsulate APP, improve the compatibility of the base material, and further improve the flame retardant effect thereof.
[0209] The present invention utilizes the condensed phase flame retardant mechanism of SiO2@APP and MCA and the gas phase flame retardant mechanism of SiO2@APP and CaG. The combination of the two can effectively improve the carbon residue rate and thermal stability of the material, and the flame retardant effect is better than when the two are used alone.
[0210] The present invention optimizes the ratio of the SiO2@APP, MCA and CaG intumescent flame retardant system, effectively reduces the peak value of the heat release rate and the total heat release of the material, and the material has good self-extinguishing property and excellent flame retardant performance.
Claims
1. Preparation method of microencapsulated modified high-efficiency intumescent flame retardant system, Features: Includes the following: To silicon dioxide (SiO 2 ) capsule material solution, ammonium polyphosphate (APP) and an emulsifier are added to perform in-situ polymerization to obtain ammonium polyphosphate (APP) as the core material and silicon dioxide (SiO 2 ) is a microencapsulated high-efficiency flame retardant system with microencapsulated ammonium polyphosphate (SiO 2 @APP); Melamine cyanurate (MCA), calcium gluconate (CaG) and microencapsulated ammonium polyphosphate (SiO 2 @APP) compound to form SiO 2 @APP / MCA / CaG intumescent flame retardant system.
2. The method for preparing the microencapsulated modified high-efficiency intumescent flame retardant system according to claim 1, Features: SiO 2 @APP / MCA / CaG intumescent flame retardant system preparation method, the specific process is as follows: A. Add ionized water and anhydrous ethanol and heat to 45°C; B. Add ammonium polyphosphate (APP) to the mixed solution and stir and disperse the emulsifier evenly; C. Continue to add ammonia water and adjust the pH value to 9-10; D. Continue to add ethyl orthosilicate dropwise; E. Stir the reaction at 45°C for 2 hours, filter, and wash with deionized water and anhydrous ethanol; F. Place in a drying oven at 80°C and dry for 24 hours to obtain microencapsulated ammonium polyphosphate (SiO 2 @APP); G. Add melamine cyanurate (MCA) and calcium gluconate (CaG) to obtain an intumescent flame retardant system.
3. The method for preparing the microencapsulated modified high-efficiency intumescent flame retardant system according to claim 2, Features: The microencapsulated ammonium polyphosphate (SiO 2 @APP) components and the number of each component are as follows: 50 parts of ammonium polyphosphate 19.85 parts of tetraethyl orthosilicate Emulsifier 0.5 parts 40 parts of ionized water 112 parts of anhydrous ethanol 8 parts of ammonia water.
4. The method for preparing the microencapsulated modified high-efficiency intumescent flame retardant system according to claim 2, Features: Step A: Add ionized water and anhydrous ethanol and heat to 45°C. The specific process is as follows: First, add 40 parts of deionized water and 112 parts of anhydrous ethanol into a 500 mL three-necked flask equipped with a reflux condenser, a thermometer, and a stirrer; Then, heat to 45°C in a water bath.
5. The method for preparing the microencapsulated modified high-efficiency intumescent flame retardant system according to claim 2, Features: Step B: Add ammonium polyphosphate (APP) to the mixed solution, and stir and disperse the emulsifier evenly. The specific process is as follows: First, add 50 parts of ammonium polyphosphate (APP) and 0.5 parts of emulsifier to the beaker solution; Then, stir and disperse evenly.
6. The method for preparing the microencapsulated modified high-efficiency intumescent flame retardant system according to claim 2, Features: Step D: Continue to add ethyl orthosilicate dropwise, the specific process is as follows: 19.85 parts of ethyl orthosilicate were added dropwise to the system solution with a pH value of 9-10 within 30 minutes.
7. The method for preparing the microencapsulated modified high-efficiency intumescent flame retardant system according to claim 2, Features: Step E: Stir the reaction at 45°C for 2 hours, filter, and wash with deionized water and anhydrous ethanol. The specific process is as follows: First, place the beaker in a 45°C constant temperature water bath and continue the reaction for 2 h; Then, the stirring speed during the reaction was 700 r / min; Then, filter and obtain a white precipitate, which is microencapsulated ammonium polyphosphate (SiO 2 @APP); Finally, wash with deionized water and anhydrous ethanol.
8. The method for preparing the microencapsulated modified high-efficiency intumescent flame retardant system according to claim 2, Features: Step G: adding melamine cyanurate (MCA) and calcium gluconate (CaG) to obtain an intumescent flame retardant system, and the specific process is as follows: First, 0-20 parts of microencapsulated ammonium polyphosphate (SiO 2 @APP) add 0-5 parts of melamine cyanurate (MCA); Then, 0-5 parts of calcium gluconate (CaG) are added to obtain an intumescent flame retardant system.
9. Application of microencapsulated modified high-efficiency intumescent flame retardant system, Features: Includes the following: First, add microencapsulated ammonium polyphosphate (SiO 2 @APP), melamine cyanurate (MCA), and calcium gluconate (CaG) are dissolved in epoxy resin (EP) a glue and stirred to disperse evenly; Then, add epoxy resin (EP) b glue at a mass ratio of a:b=3:1, let it stand for 5 minutes, and pour it into a silicone mold of specified size after the bubbles dissipate, and cure it at room temperature for 24 hours; Finally, the flame retardant EP composite material is demoulded.
10. Use of the microencapsulated modified high-efficiency intumescent flame retardant system according to claim 9, Features: The flame retardant EP composite material components and the number of each component are as follows: Microencapsulated ammonium polyphosphate 0-20 parts 0-5 parts of melamine cyanurate Calcium gluconate 0-5 parts Epoxy resin A glue 52.5 parts 17.5 parts of epoxy resin B glue.
Citation Information
Cited By
Flame-retardant antibacterial polyurethane material and preparation method thereof
CN122213658A
Preparation method of intumescent flame-retardant coating adhesive and fireproof polyester fabric
CN122504071A
